Efficacy and Safety of Berberine Alone for Several Metabolic Disorders: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Ye, Yu; Liu, Xiufen; Wu, Ninghua; Han, Yanqi; Wang, Jiawen; Yu, Yuandong; Chen, Qingjie (Frontiers in Pharmacology, 2021)
Background: Metabolic activity is the basic life activity of the human body and the fundamental for maintaining body functions. With the improvement of living standards, the incidence of metabolic disorder diseases is also increasing year by year. Most metabolic disorder diseases lack a radical cure, and the existing treatment measures is delayed the course of the disease and reduced complications. At present, most of the clinical treatment strategies and meta-analysis for metabolic disorder diseases are combined medicines, however, there is not enough evidence to disclose the therapeutic effect of the berberine treatment without any combination and the possible factors affecting the efficacy. The purpose of this study is to conduct a systematic review and meta-analysis of the literature to evaluate the therapeutic effect of Berberine in metabolic disorder disease, To further understand the effect of Berberine treatment alone and the possibility of the facets may influence the effect, we have formulated strict inclusion criteria and selected more reliable data for meta-analysis through more refined screening strategies, hoping to provide evidence and guidance for clinical decision-making. Methods and results: Using Meta-analysis of "Cochrane Handbook for Systematic Reviews of Interventions" as guidelines, we searched PubMed, GeenMedical, Cochrane library, CNKI for trails reporting clinical treatment data of Berberine. To increase confidence in results, another 417 trails is included through other sources. Among the 1660 related documents retrieved from the four databases, 18 eligible documents were selected for analysis. Due to the differences in trial design and measurement units, we used the Standardized Mean Differences (SMD) method to eliminate the differences and then summarize the data for analysis. The main factors analyzed are TG, TC, LDL, HDL, HOMA-IR, and FPG. Random-effects model analysis TG (SMD: 0.94; 95%CI: 0.49,1.38; p=0.00), TC (SMD: 1.06; 95%CI: 0.64, 1.48; p=0.00), LDL (SMD: 1.77; 95%CI: 1.11,2.44; p=0.00), HDL (SMD: -1.59; 95%CI: -2.32,-0.85; p=0.00), HOMA-IR (SMD: 1.25; 95%CI: 0.25,2.24; p=0.01), FPG (SMD: 0.65; 95%CI: 0.28,1.03; p=0.00). Conclusions: Berberine can improve obesity and hyperlipidemia by regulating metabolism to reduce TG, TC, LDL and increase HDL; reduce insulin resistance to improve type 2 diabetes, and prevent diabetic encephalopathy.